Algebraicity of Hodge Loci for Variations of Hodge Structure - Cattani, Eduardo (2014)
These notes should be seen as a companion to [8], where thealgebraicity of the loci of Hodge classes is proven without appealing to theHodge conjecture. We give explicit detailed proofs in the case of variationsof Hodge structures over curves and surfaces which, we hope, help clarify thearguments in [8], as well as some generalizations, consequences and conjecturesbased on those results.